2023
DOI: 10.1021/acsaem.3c01693
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced High-Temperature Thermoelectric Performance of Yb4Sb3 via Ce/Bi Co-doping and Metallic Contact Deposition for Device Integration

Sylvain Le Tonquesse,
Hugo Bouteiller,
Yoshitaka Matsushita
et al.

Abstract: Thermoelectrics (TE) for very high temperatures (>800 K) have numerous potential applications in heavy industry and space exploration. This article focuses on the compound Yb4Sb3 which is a promising p-type counterpart to the structurally related and high-performance n-type RE3Te4 (RE = Nd, La, Pr) for the fabrication of high-temperature TE modules. A quick and efficient method for synthesizing pure and fully dense Yb4Sb3 samples was developed and optimized using high-energy ball milling followed by reactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, compositions with x ≤ 0.3 display no LaSb impurities and exhibit undistorted peaks, signifying successful substitution of La and Bi for Yb and Sb, respectively, in the structure. This solubility limit is slightly lower than that observed in the Ce-inserted Ce x Yb 4− x Sb 2.8 Bi 0.2 solid solution ( x = 0.5), 22 mainly owing to the higher atomic radius of La atoms (1.95 Å) compared with Ce atoms (1.85 Å). The refined cell parameters are displayed in Fig.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…However, compositions with x ≤ 0.3 display no LaSb impurities and exhibit undistorted peaks, signifying successful substitution of La and Bi for Yb and Sb, respectively, in the structure. This solubility limit is slightly lower than that observed in the Ce-inserted Ce x Yb 4− x Sb 2.8 Bi 0.2 solid solution ( x = 0.5), 22 mainly owing to the higher atomic radius of La atoms (1.95 Å) compared with Ce atoms (1.85 Å). The refined cell parameters are displayed in Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Very recently, we used a similar strategy with partial Bi substitution on Sb sites while a partial amount of Yb atoms were replaced by Ce atoms. 22 Findings from this study demonstrated a significant enhancement in the thermoelectric properties of the Ce-substituted solid solution, motivating further exploration into the transport properties of the La-substituted solid solution.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation